Superficial Acral Fibromyxoma: A Report of Two Cases with CD68 Expression - Huang Q; Li Y; Niu M; Chen G (Clinical, Cosmetic and Investigational Dermatology, 2024)
Qingan Huang,1,* Yuan Li,2,3,* Mu Niu,2 Gaihe Chen4 1Department of General Ward, the Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China; 2Department of Cosmetic Dermatology, the Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China; 3Department of Dermatology, the First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 4Department of Dermatology, the Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gaihe Chen, Department of Dermatology, the Fifth People’s Hospital of Hainan Province, No. 8 Longhua Road, Longhua District, Haikou, Hainan, 570100, People’s Republic of China, Email 279701157@qq.com Mu Niu, Department of Cosmetic Dermatology, the Fifth People’s Hospital of Hainan Province, No. 8 Longhua Road, Longhua District, Haikou, Hainan, 570100, People’s Republic of China, Email 382219948@qq.comAbstract: Superficial Acral fibroma (SAF), also known as osteofibroma, is a rare fibromatous tumor primarily involving superficial soft tissues. Clinically, SAF typically manifests as a slow-growing, solitary, well-defined nodule or mass. Although these lesions are generally asymptomatic, some cases may present with associated pain, often linked to a history of trauma. SAF lesions commonly exhibit hemispherical, polypoid, or warty growths, with occasional occurrences of ulceration and bleeding.The majority of SAFs express CD34 and CD99, but in the two cases we report, there was diffuse expression of CD34 and focal positive expression of CD68. CD68 positivity suggests a propensity for tumor cells to metastasize to secondary sites. Notably, previously reported cases of single SAF did not display positive CD68 expression, indicating a potential association with other aggressive tumors. However, the current clinical and pathological manifestations do not clarify the diagnosis of additional malignant tumors. Consequently, regular postoperative monitoring of the patient from the aforementioned two cases is essential to detect the presence of other malignant tumors. The significance of CD68-positive expression in this case lies in its potential association with such tumors.Keywords: superficial acral fibromyxoma, immunohistochemistry, CD34, CD68